Definisi dan Keterkaitan Mantuq dan Mafhum, Dzahir dan Mu’awwal, Nasakh, Muradif dan Musytarak - Andi Silva Quadsajul; Ahmad Faidillah; Muhammad Naufal Ma’rifat; Kurniati Kurniati (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The study of ushul fiqh is very closely related to the Koran and Sunnah. Both of them are the core sources of Islamic sharia law which are used as proof which are processed by ushuliyah rules in determining sharia laws. This research aims to explain the essence of Ushuliyyah rules, especially regarding Mantuq and Mafhum, Dzahir and Mu'awwal, Nasakh, Muradif and Musytarak. This research is library research with the subject and object coming from library materials in the form of ushul al-fiqih books and fiqh journals. The results of this research came to the conclusion that the fuqaha used various methods to understand the texts in the Al-Quran and hadith. One way is to use ushuliyah rules such as mantuq and mafhum, dzahir and mu'awwal, nasakh, muradif and musytarak.